1984
DOI: 10.3168/jds.s0022-0302(84)81321-1
|View full text |Cite
|
Sign up to set email alerts
|

Retention Data for Antibiotics Commonly Used for Bovine Infections

Abstract: This study was designed to observe the maximum time that various antibiotics used in different ways as treatment of bovine infections persisted in milk after final treatment. Both Delvotest-P and Bacillus stearothermophilus (Difco) disc assay procedures were utilized for detection of antibiotic preparations used for treatment of mastitis. None persisted in milk longer than specified on their respective labels. Because antibiotic residues were detected in milk consequent to treatment for intrauterine infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Most cows treated IU with up to 2 million units of PPG will have detectable milk residues for < 24 hours, but milk residues detected up to 80 hours have been reported. [16][17][18] Unfortunately, data regarding tissue depletion after IU administration of PPG do not exist. In a limited number of cattle, after IU administration, PPG was not detectable in serum at 10 hours or in urine at 24 hours, 17,19 suggesting that modestly extending the label withdrawal interval to 12 days would prevent violative tissue residues.…”
Section: Intrauterine Administrationmentioning
confidence: 99%
“…Most cows treated IU with up to 2 million units of PPG will have detectable milk residues for < 24 hours, but milk residues detected up to 80 hours have been reported. [16][17][18] Unfortunately, data regarding tissue depletion after IU administration of PPG do not exist. In a limited number of cattle, after IU administration, PPG was not detectable in serum at 10 hours or in urine at 24 hours, 17,19 suggesting that modestly extending the label withdrawal interval to 12 days would prevent violative tissue residues.…”
Section: Intrauterine Administrationmentioning
confidence: 99%
“…In countries such as Canada and the USA, milk samples from farms are routinely monitored by government or industry for the presence of antibiotic residues (Barnard 1982, Booth andHarding 1986). Milk is considered to be adulterated if the antibiotic residues exceed tolerance limits set by the Food and Drug Administration (USA) (Bishop et al 1984). In India, such legislation has not yet been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have studied the persistence of antibiotics in cow milk when used for reproductive tract infections, mainly in the uterus. Some of them have found evidence of antibiotic residues in milk in the first milkings (24 to 48 h) after the intrauterine administration of suppositories, infusions, or tablets of penicillin, streptomycin, or tetracycline (Miller and Bergt, 1974;Black et al, 1979;Bishop et al, 1984).…”
mentioning
confidence: 99%
“…According to Bishop et al (1984), after the administration of antibiotics for vaginal infections, the passage of antibiotics from the vaginal membrane into blood and milk is possible. Several authors have found antibiotic residues in milk after the intrauterine administration (Miller and Bergt, 1974;Black et al, 1979 ., 1984).…”
mentioning
confidence: 99%